EVALUATION OF RECREATIONAL ACTIVITIES IN THE CONTEXT OF CONSUMPTION PRODUCTS CLASSIFICATION - Uğur Keskin; Alican Bayram (ümit doğan üstün, 2018)
The purpose of this study is to explain the recreation activities that have become increasingly prevalent in recent years. For this purpose, the focus is on the basic research question that can be expressed as "Is it possible to classify recreational activities within the context of consumer products?" This question has been tried to give answers on the classification of consumer products, adequacy of recreational activities and adequacy of explanations. The search for the answer was carried out through a theoretical discussion method conducted through literature review. Although classification of consumer goods is widely used in scientific fields such as business and marketing, the classification is not sufficiently recognized in the field of sports science and therefore is not used. Classification of consumer products, which gives the opportunity to explain and categorize every kind of consumer product, depending on the qualities it has, makes it possible to take recreational activities in the same sense. As a result of the study carried out under the article, classification of consumer goods; to allow recreational activities to be described within their limitations, and the underlying question of this work is the result of a series of concordant explanations between the field of business science and the field of sports science.